SISTEM INFORMASI GEOGRAFIS (SIG) PELAYANAN KESEHATAN - Liman Hege, Yeremias Budi; Lestari, Uning; Kumalasari, Erna (Jurnal Script, 2014)
ABSTRACTThe use of computer and software have been increasing significantly nowadays in most aspects of lifeÂ  including social, culture, politic, economic, agriculture, and health as well. The Geographic Information System (GIS) provides health service information for public in Yogyakarta. Geographic Information System (GIS) helps public or related institutions to obtain informasi about location of health service places in Yogyakarta. Hospital data, public health centre data, clinic data as well as pharmacy data in the Yogyakarta were needed in the process of regulating this Geographic Information System (GIS). The supporting tools used were not only PHP code editor and Notepad, but also MySQL for arranging database. In collecting the data, the writer used Interview method, obsein thrvasi method and references study method. This research is aimed to regulate the Geographic Information System (GIS) to help public in finding public health service places. By using this Geographic Information System (GIS), the development of public health service information becomes Uptodate.Â Keywords: Geographic Information System, GIS, health service, system, information